2008
DOI: 10.2341/07-61
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cement Shade and Water Storage on the Final Color of Leucite-reinforced Ceramics

Abstract: Operative Dentistry, 2008, 33-4, 386-391 L Karaagaclioglu • B Yilmaz Clinical RelevanceLuting cement under 0.8 mm thick leucite-reinforced ceramic changed the final color of the ceramic and could be seen by the human eye. Therefore, clinicians may prefer to use try-in pastes or polymerized luting composite shade guides to compensate for the change in color of definitive restorations, such as laminate veneers. The final color differences between ceramics luted with cements in A1 and A3 shades were not clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 21 publications
0
51
0
4
Order By: Relevance
“…The curing light can pass through more translucent materials more readily than through more opaque ceramics. Therefore, a greater degree of conversion will lead to more stable color after polymerization 28) , and the use of the lost-wax technique in the fabrication process improved marginal accuracy and provided increased options of shading, with a layering technique during the fabrication of ceramic veneers which facilitated more shade selection and better esthetic results 29) . In contrast, the presence of leucite content in IPS Empress Esthetic Press is critical, due to the higher incidence of crack deflection and thermal contraction mismatch compared with glassy matrix, influencing the mechanical and physical properties of the ceramics 30) .…”
Section: Discussionmentioning
confidence: 99%
“…The curing light can pass through more translucent materials more readily than through more opaque ceramics. Therefore, a greater degree of conversion will lead to more stable color after polymerization 28) , and the use of the lost-wax technique in the fabrication process improved marginal accuracy and provided increased options of shading, with a layering technique during the fabrication of ceramic veneers which facilitated more shade selection and better esthetic results 29) . In contrast, the presence of leucite content in IPS Empress Esthetic Press is critical, due to the higher incidence of crack deflection and thermal contraction mismatch compared with glassy matrix, influencing the mechanical and physical properties of the ceramics 30) .…”
Section: Discussionmentioning
confidence: 99%
“…15 Similarly, a 0.8 mm thick IPS Empress 1 ceramic specimen was not affected by the shades of luting cements (Vita A1 and A3, RelyX ARC). 16 These different results may be due to variations in the experimental design of the studies, such as shade of the ceramic specimens, the substrate materials, the luting cements and the color-measuring instruments. In fact, if these factors are not ideally coordinated, an optimal esthetic appearance cannot be created.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have reported the importance of understanding the influence of underlying color on the clinical appearance of a final crown. [11][12][13][14][15][16][17][18] One study demonstrated a range of ceramic core translucency, with Empress 2 1 having more translucency than a zirconia core. 12 The glazing cycle decreased opacity of most all ceramic crown materials, except the completely opaque InCeram 1 zirconia.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Furthermore, with translucent ceramic restorations, shade could be optimized with resin-based luting cements. 13 Conventional resin luting cements require pretreatment of the prepared dentin, which is technique-sensitive and time-consuming. For this reason, recently, self-adhesive resin luting cements have been promoted, because they do not require pretreatment of dentin.…”
Section: Introductionmentioning
confidence: 99%